Systemic Sclerosis (Scleroderma) with Hypothyroidism in a Four and Half Year Old Child: A Case Report - Rahman, SA; Sultana, J; Huque, SS; Kawser, CA (Journal of Bangladesh College of Physicians and Surgeons, 2007)
A four and half years old boy was admitted in the Paediatric ward of Bangabandhu Sheikh Mujib Medical University (BSMMU) with the complaints of tightening of skin at different parts of the body and contracture of the joints. Three years back he was admitted in the same hospital for weakness, less activity and constipation. At that time he was diagnosed as a case of hypothyroidism. On examination the boy had expressionless face, pinched nose and microstomia. There was tightening and hardening of skin all over the body associated with sclerodactyly and contractures and flexion deformities of all the distal joints of the extremities. From the history, clinical findings and supportive investigations the boy was diagnosed as a case of systemic sclerosis with hypothyroidism. (J Bangladesh Coll Phys Surg 2007; 25 : 47-51)